KEPUASAAN IBU PADA PELAYANAN KESEHATAN IBU DAN ANAK DI UPTD PUSKESMAS JAPAH KABUPATEN BLORA - Sri Purwati; Sri Rahayu; Kuswanto Kuswanto (JURNAL KEBIDANAN, 2017)
Patient dissatisfaction synonymous with complaints against the service. Patient satisfaction depends on the quality of service (Supranto J, 2006). Whether or not the service can be seen from how big the dimension of service quality through five principles of Service Qualit), like: Tangible (physical evidence), Reliability (reliability), responsiveness (Responsiveness), Assurance (Assurance), Empathy (Empathy) (Hardiyansyah, 2011). The purpose of this study was to determine faktot-factors associated with maternal satisfaction of visitors poly KIA.This research was conducted in a poly KIA UPTD Japah PHC in March to May 2016 This research is a correlation with cross sectional approach, using the method of survey research subjects mother visitors poly KIA and PONED with the samples according to the criteria of 100 respondents with accidental sampling method. The data were analyzed using univariate and bivariate Continuity Correction.The results showed a good percentage of satisfaction dimensional aspect more than the percentage that is not good. The results of the percentage satisfied to the satisfaction aspect as much as 66%, both aspects of physical evidence as much as 72%, good reliability aspects as much as 77%, the responsiveness of both aspects as much as 62%, better guarantee as much as 64%, and a good empathy as much as 66%. Continuity Correction of test results on five dimensions of quality that physical evidence, responsiveness, kehandalaan, assurance and empathy showed that no significant relationship with patient satisfaction.